Malnutrition by European Society for Clinical Nutrition and Metabolism criteria predicts prognosis in patients with gastrointestinal and hepatobiliary–pancreatic cancer. (April 2021) - Aotani, Nozomi; Yasui-Yamada, Sonoko; Kagiya, Natsumi; Takimoto, Mami; Oiwa, Yu; Matsubara, Atsumi; Matsuura, Sayaka; Tanimura, Mayu; Tani-Suzuki, Yoshiko; Kashihara, Hideya; Saito, Yu; Nishi, Masaaki; et al.
Summary: Background & aims: The European Society for Clinical Nutrition and Metabolism (ESPEN) proposed the ESPEN diagnostic criteria (EDC) for malnutrition in 2015. There is no report on the association between the EDC and prognosis in patients with gastrointestinal (GI) and hepatobiliary–pancreatic (HBP) cancer. This study aimed to (1) determine the prevalence of EDC malnutrition, (2) investigate the validity of the EDC as a nutritional and prognostic indicator, and (3) examine which components of the EDC are most related to long-term prognosis in patients with GI and HBP cancers. Methods: A total of 634 patients with primary GI and HBP cancers who underwent their first resection surgery between July 2014 and March 2018 were retrospectively recruited. According to the EDC, patients were divided into malnourished and non-malnourished groups. Clinical parameters and survival between these two groups were compared. The prognostic effects of the EDC and the EDC components were analyzed using Cox proportional hazard models. Results: The prevalence of EDC malnutrition was 22%. Anthropometric data and biochemical data were associated with EDC malnutrition. The 5-year survival rate was lower in the malnourished group (72%) than in the non-malnourished group (73%; P = 0.007). The multivariate analysis demonstrated that the malnourished group was an independent risk factor for mortality (hazard ratio = 1.70 in the malnourished group; 95% confidence interval 1.08–2.63; P = 0.024). Among EDC components, body mass index (BMI) of <18.5 kg/m 2 was an independent poor prognostic factor. Conclusions: EDC malnutrition is associated with poor postoperative long-term prognosis. Among the EDC components, BMI of <18.5 kg/m 2 is most associated with prognosis in patients with preoperative GI and HBP cancers. Highlights: We analyzed patients with gastrointestinal and hepatobiliary–pancreatic cancer. The prevalence of ESPEN diagnostic criteria (EDC) malnutrition was 22%. EDC malnutrition was a significant risk factor for 5-year mortality. Among EDC components, BMI <18.5 kg/m 2 was strongly associated with poor prognosis.